Determining factors for neonatal mortality in a city in the Southern Region of Brazil - Ferrari, Rosangela Aparecida Pimenta; Bertolozzi, Maria Rita; Dalmas, Jose Carlos; Girotto, Edmarlon (Revista da Escola de Enfermagem da USP, 2013)
This is an ecological quantitative study to identify risk factors that determined neonatal death between the years of 2000 to 2009 in Londrina, Paraná, using data from Birth Certificates, Death Certificates and Infant Death Investigation Forms. The variables maternal age, years of education, family income, occupation, marital status, type of delivery, and number of prenatal appointments were not associated to neonatal death. To the contrary, birth weight, gestational age, Apgar score at 1 and 5 minutes, and place of birth were identified as statistically significant variables. More than 73.0% of newborns died within early neonatal period. The predominant basic cause of death was perinatal problems (77.7%), 72.6% of which were preventable, and the majority of which could be reduced with adequate control over pregnancy/birth. These results highlight the need for investments in prevention of premature delivery by improvement of health care in prenatal and birth periods, in an equanimous, accessible and comprehensive manner in all levels of maternal and child health care.